2019
DOI: 10.3390/electronics8101099
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Transition of Copper Oxide by the Incorporation of Nitrogen

Abstract: In the present study, the effects of nitrogen incorporation on the transition of a p-type copper oxide semiconductor are investigated. The properties of sputtered copper oxide and nitrogen-incorporated copper oxide are evaluated and compared at various nitrogen gas flow rates. The results indicate that the addition of nitrogen results in an increased optical bandgap, accompanied by significantly reduced tail states compared to pristine copper oxide. In addition, X-ray diffraction and X-ray photoelectron spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…The first peak is due to metal-oxygen bonds (Cu-O) centered at 530.15 eV, and the second is due to oxygen-related defects, such as oxygen vacancies (Vo), centered at 531.55 eV. In general, the metal-oxygen peaks and the oxygen-related defect peaks in metal oxides are near 530.6 eV and 531.9 eV, respectively [56], similar to those found in this work.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…The first peak is due to metal-oxygen bonds (Cu-O) centered at 530.15 eV, and the second is due to oxygen-related defects, such as oxygen vacancies (Vo), centered at 531.55 eV. In general, the metal-oxygen peaks and the oxygen-related defect peaks in metal oxides are near 530.6 eV and 531.9 eV, respectively [56], similar to those found in this work.…”
Section: Resultssupporting
confidence: 84%
“…However, the presence of the CuO phase (Cu(II) species) is confirmed by the detection of the satellites [17]. In Figure 5(a), it is observed that the intensity of the satellite 9 Journal of Nanomaterials decreases with the increase of the glucose content, suggesting a decrease in CuO content [56].…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…In addition, other characteristics of this method are the high deposition rate, dense layer formation, good surface flatness, and low substrate temperature [7]. to CuO [9]. This is beneficial because it becomes easier to induce electron flow, which means better efficiency.…”
Section: Introductionmentioning
confidence: 99%